2019
DOI: 10.3390/ijms20194664
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Fabrication of Cytocompatible PLLA-Magnetite Nanoparticle Composite Scaffolds

Abstract: Magnetic biomimetic scaffolds of poly(L-lactide) (PLLA) and nanoparticles of magnetite (nFe3O4) are prepared in a wide ratio of compositions by lyophilization for bone regeneration. The magnetic properties, cytotoxicity, and the in vitro degradation of these porous materials are closely studied. The addition of magnetite at 50 °C was found to produce an interaction reaction between the ester groups of the PLLA and the metallic cations of the magnetite, causing the formation of complexes. This fact was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The results showed that different concentrations of extracts had no significant influence on the cell growth relative to the corresponding negative control group, and there was no significant difference between different concentrations of extract ( Figures 5(c)-5(e)). It can be concluded that PLLA is nontoxic and suitable for in vivo study, which is consistent with other literature reports [30][31][32].…”
Section: Biomed Research Internationalsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that different concentrations of extracts had no significant influence on the cell growth relative to the corresponding negative control group, and there was no significant difference between different concentrations of extract ( Figures 5(c)-5(e)). It can be concluded that PLLA is nontoxic and suitable for in vivo study, which is consistent with other literature reports [30][31][32].…”
Section: Biomed Research Internationalsupporting
confidence: 91%
“…These scaffolds not only meet the requirements of distraction but also have a porous structure to guarantee the interaction between the periosteum and bone cortex. Researchers also used other advanced technologies to prepare porous PLLA materials, such as supercritical air foaming and freeze drying [30][31][32]. These state-of-the-art systems can adjust the porosity or composition of the material itself, but they all need some special mold processing to achieve a spatial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have attracted increasing scientific interest, due to their numerous biomedical applications. Among such materials, Iron-Oxide NanoParticles (IONPs) awaken special interest, because of their magnetic properties, biocompatibility, and nanometric sizes that can interact at the cellular, subcellular, and even molecular levels [1,2]. As iron is a metal that is found in haemoglobin and myoglobin in the form of ferritin, the particles are non-toxic, although particle aggregation can be dangerous [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…At particle sizes of less than 30 nm, their diameters range between 5 and 100 nm. Each particle produces a nanoscale magnetic field and acts as a single magnetic domain, showing superparamagnetic behavior [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Díaz prepared PLLA nanofiber membrane by electrospinning. When conducting in vitro cell culture experiments, it was found that the orientation of the nanofiber membrane itself had a contact guiding effect on osteoblasts (Díaz et al, 2019 ).…”
Section: Preparation Of Magnetic Nanomaterialsmentioning
confidence: 99%